(untitled) (Medico Legal Update, 2019)
In this study, the shape and function of a mammography compression paddle was revised and investigated with regard to contrast and image quality in patients with pectus carinatum. The center of the novel compression paddle surface had a radius of curvature of the contact area with the chest wall. The double structure of the compression paddle frame provided sufficient contact with the chest wall and reduced pain.. Springs in the back allowed an open space of 30 mm. we compared the increasing rate of total area and posterior nipple line (PNL) and the image surface plot. With the newly developed compression paddle, the averaged increasing rate of the total area in 10 patients with pectus carinatum was 9.65% and 6.96% in the craniocaudal (CC) and mediolateral-oblique (MLO) directions, respectively; the averaged increasing rate of the PNL was 9.18% and 4.55% in the CC and MLO directions, respectively; and the averaged increasing rate of the breast length side chest wall was 3.97% in the CC direction. The newly developed compression paddle appeared to contain more breast tissue without degradation in image contrast and quality. The novel breast compression paddle was streamlined, thereby reducing friction with the chest wall. It also contained substantial breast tissue because the springs make it possible to move back and forth to match breast chest size. The developed compression paddle will provide a wider diagnostic range for mammography